Fibrinogen Plasma Levels in an Apparently Healthy General Population – Relation to Environmental and Genetic Determinants - Margaglione, Maurizio; Cappucci, Giuseppe; Colaizzo, Donatella; Pirro, Leonardo; Vecchione, Gennaro; Grandone, Elvira; Minno, Giovanni Di (Thrombosis and Haemostasis, 1998)
Elevated fibrinogen levels are an independent risk factor for cardiovascular ischemic disease. We investigated the relationship between cardiovascular ischemic risk factors, the fibrinogen Bβ-chain G/A-455 polymorphism and plasma fibrinogen levels in 989 apparently healthy subjects. Fibrinogen values were higher in subjects with C reactive protein (C-RP) > 0.33 mg/dl, BMI > 23.9 kg/m2, total cholesterol > 4.84 mmol/l, triglycerides >1.02 mmol/l, PAI-1 antigen >12.2 ng/ml, carriers of the A allele, first-degree relative history of coronary artery disease, or consuming >10 cigarettes per day (p <0.01). Men and ethanol drinkers showed lower plasma fibrinogen levels (p <0.01). The multivariate analysis confirmed the independent effect of C-RP, age, BMI, total cholesterol, gender, PAI-1, -455 G/A polymorphism, (p <0.05). BMI, total cholesterol, PAI-1, alcohol and smoking habit raised with the increase of age and differed between sexes. The A-455 allele increasing effect was significant in women, especially in subjects aged <30 years, and in men aged <43 years. These results indicate that environmental factors contributed to a larger extent to fibrinogen variability, whereas the A-455 allele was associated with a steeper increase in younger age quartiles.